Optimalisasi Peranan Ruang Terbuka Hijau Sebagai Ruang Publik di Alun-Alun Kota Surabaya (Lembaga Pengembangan Kinerja Dosen, 2021)
This study aims to determine the optimization of the function of green open space as a public space in Surabaya Square. In this case, the researcher uses several concepts such as optimization, public space and green open space. By using qualitative research methods, it means that qualitative research provides space for a research process that is closer to the object of research, where researchers reveal and understand unknown social phenomena by constructing a holistic and complex picture. And from this research, the results show that in optimizing green space as a public space in Surabaya Square it is still not said to be optimal, because in the standard criteria of a good public space there are still several aspects that need to be addressed and the need to add some public facilities.